DEFIANCE OF WOMEN WITH DISABILITY - KUMAR K, SATHISH (Innovare Journal of Education, 2019)
Person with disability are the socially, educationally and economically disadvantaged. And then women with disability persons are suffer lot. Analysis of the causes of disability from a medical or bio-centric standpoint tends to emphasise disease, hereditary and birth defects over systemic and environmental factors. Genetic factors and lack of access to basic services can also lead to a person becoming disabled. . Provincial commissions have reported inadequate and insufficient accommodation arrangements in schools. Information about the financial and health impacts of entering the open workplace is hard to find, there is limited or delayed access to open employment services. Some jurisdictions reported that complaints are increasing for these disabilities. While there is increased awareness about mental health, persons with mental health problems and illnesses are still facing many barriers in accessing education, including lack of services and adequate accommodation due to insufficient funding, as well as stigma and discrimination. Policy-makers might consider that the highly resource-intensive, tailored forms of support recommended here are too costly to contemplate given competing priorities.